PREVENTIVE DETENTION OF CHILDREN UNDER MALAYSIAN LAWS: A CASE FOR REFORM (UUM Journal of Legal Studies, 2020)
Preventive detention refers to the incarceration of an individual who has not yet been convicted, to prevent him from causing harm or endangering the community in some unspecified way. It can be seen as the deprivation of an individual’s liberty based on the belief that he may be a danger to others. The issue of preventive detention of children is very controversial and has attracted debate among various legal scholars. In Malaysia, provisions contained in specific statutes that aim to prevent terrorism or threats to national security have been invoked to justify the preventive detention of children. The practice and application of these statutory provisions on children have been subjected to various criticism. This paper aims to analyze current Malaysian laws pertaining to the preventive detention of children. It encompasses qualitative research of doctrinal and comparative nature. It will critically analyze legal issues in this area with reference to international standards and practices of other legal systems. The study concludes that the legal reform of the current Malaysian legal framework on this aspect is urgently needed to protect the rights and interests of children during the juvenile justice processes. Therefore, the study provides recommendations towards the improvement of the existing laws and policies on the preventive detention of children.